The characteristics of preeclampsia among patients delivered through caesarean section at Sanglah General Hospital, Denpasar, Bali in 2018 - Anindita Pramanik; Ida Bagus Gede Fajar Manuaba; Anak Agung Putra Wiradnyana (DiscoverSys Inc., 2019)
Background: Preeclampsia is an exclusive disorder in pregnancy characterised by hypertension as well as proteinuria and is the primary cause of mortality and morbidity of pregnant women. This study aims to determine the characteristics or risk factors in preeclampsia patients who delivered through caesarean section within the period of January 1st to December 31st 2018 in Sanglah General Hospital Denpasar.Methods: This study used a retrospective descriptive study design by using 34 samples of preeclampsia patients in 2018 who underwent caesarean delivery in Sanglah General Hospital Denpasar. The characteristics of these pregnant women are categorized into their age, education level, Body Mass Index (BMI), ethnicity, occupation, education level, previous history of preeclampsia, family history of preeclampsia, existing chronic hypertension, parity, number of fetus in womb, frequency of Antenatal Care (ANC), and registration method. Data were analysed by SPSS version 17 for windows.Results: The preeclampsia sufferers were dominated by the age group of 20-35 years as many as 27 people (79.4%). The highest body mass index is in the 1 obese group of 10 people (29.4%). The majority of respondents were from Bali (61.8%). Working women were predominant (67.6 %), followed by SMA education level (14.7%), existing chronic hypertension (5.9%), nulliparous (41.1%), single fetuses (94.1%), and total frequency of ANC to midwife/obstetrician consisting about 61.8%.Conclusion: It can be concluded that the majority of the patients were in the age range of 20-35 years, were Balinese and had a BMI range of Obese I. Moreover, most the preeclampsia patients in this study were working women and had an education level mostly in SMA